The Kaiser Permanente Northern California research program on genes, environment, and health (RPGEH) pregnancy cohort: study design, methodology and baseline characteristics. Issue 1 (December 2016) - Hedderson, M.; Ferrara, A.; Avalos, L.; Van den Eeden, S.; Gunderson, E.; Li, D.; Altschuler, A.; Woo, S.; Rowell, S.; Choudhary, V.; Xu, F.; Flanagan, T.; et al.
Abstract Background Exposures during the prenatal period may have lasting effects on maternal and child health outcomes. To better understand the effects of the in utero environment on children's short- and long-term health, large representative pregnancy cohorts with comprehensive information on a broad range of environmental influences (including biological and behavioral) and the ability to link to prenatal, child and maternal health outcomes are needed. The Research Program on Genes, Environment and Health (RPGEH) pregnancy cohort at Kaiser Permanente Northern California (KPNC) was established to create a resource for conducting research to better understand factors influencing women's and children's health. Recruitment is integrated into routine clinical prenatal care at KPNC, an integrated health care delivery system. We detail the study design, data collection, and methodologies for establishing this cohort. We also describe the baseline characteristics and the cohort's representativeness of the underlying pregnant population in KPNC. Methods While recruitment is ongoing, as of October 2014, the RPGEH pregnancy cohort included 16, 977 pregnancies (53 % from racial and ethnic minorities). RPGEH pregnancy cohort participants consented to have blood samples obtained in the first trimester (mean gestational age 9.1 weeks ± 4.2 SD) and second trimester (mean gestational age 18.1 weeks ± 5.5 SD) to be stored for future use. Women were invited to complete a questionnaire on health history and lifestyle. Information on women's clinical and health assessments before, during and after pregnancy and women and children's health outcomes are available in the health system's electronic health records, which also allows long-term follow-up. Discussion This large, racially- and ethnically-diverse cohort of pregnancies with prenatal biospecimens and clinical data is a valuable resource for future studies on in utero environmental exposures and maternal and child perinatal and long term health outcomes. The baseline characteristics of RPGEH Pregnancy Cohort demonstrate that it is highly representative of the underlying population living in the broader community in Northern California.